2D Modeling of Subsurface Structures Based on Gravity Data of Mount Arjuno-Welirang - Alifa Tri Handayani; M. Aryono Adhi; Supriyadi; Budi Eka Nurcahya (Physics Education Research Journal, 2025)
Indonesia is a country that has volcanoes stretching from west to east from Sumatra, Java to Sulawesi. Mount Arjuno-Welirang is a stratovolcano type volcano with an altitude of about 3,339 m (10,955) for Mount Arjuno while for Welirang it is about 3,156. Mount Arjuno-Welirang and its surroundings are composed by rocks sourced from Anjasmoro Volcano (Early Plistocene), Ringgit-Pundak-Butak Volcano (Middle Plistocene), Arjuno-Welirang Twin Volcanoes I and II (Late Plistocene), and Penanggungan Volcano. This research includes data processing and interpretation of the results of data processing.  This research was conducted using geophysical methods, namely the gravity method. The theoretical basis used is Newton's Law. Data in the form of gravity data that has been downloaded on the Land Gravity Data Website which is then processed using Surfer software, then the Magpick Software Upward Continuation process is carried out. After that, the slicing process is carried out on the residual anomaly, then the slicing results will be used to interpret using Grav2DC Software qualitatively based on the geological map as a reference. The interpretation results on the A-B and C-D tracks obtained 4 rock layers, namely volcanic breccia, lava, tuff breccia, and tuff rock. With an error value of 8.25% for incision A-B, and 3.63% for incision C-D.